2012
DOI: 10.1093/infdis/jis751
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell–Induced Components of the Sulfate Assimilation Pathway Are Major Protective Antigens of Mycobacterium tuberculosis

Abstract: New therapies to control tuberculosis are urgently required because of the inability of the only available vaccine, BCG, to adequately protect against tuberculosis. Here we demonstrate that proteins of the Mycobacterium tuberculosis sulfate-assimilation pathway (SAP) represent major immunogenic targets of the bacillus, as defined by strong T-cell recognition by both mice and humans infected with M. tuberculosis. SAP proteins displayed increased expression when M. tuberculosis was resident within host cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Sulfur assimilation is critical for M. tuberculosis survival and components of the sulfate assimilation pathway are highly expressed under conditions of sulfur limitation and within macrophages, the principal host cell for M. tuberculosis during infection. 13 , 14 Furthermore, transposon mutagenesis studies showed that genes of this pathway, including cysD , are essential for M. tuberculosis viability. 15 The upregulation of cysD within host cells, coupled with the requirement for sulfate assimilation during chronic M. tuberculosis infection, 16 suggested that expression of CysD may be modified in the host during chronic M. tuberculosis infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfur assimilation is critical for M. tuberculosis survival and components of the sulfate assimilation pathway are highly expressed under conditions of sulfur limitation and within macrophages, the principal host cell for M. tuberculosis during infection. 13 , 14 Furthermore, transposon mutagenesis studies showed that genes of this pathway, including cysD , are essential for M. tuberculosis viability. 15 The upregulation of cysD within host cells, coupled with the requirement for sulfate assimilation during chronic M. tuberculosis infection, 16 suggested that expression of CysD may be modified in the host during chronic M. tuberculosis infection.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Although SAP members are non-secreted, the proteins were recognised during the course of M. tuberculosis infection in mice and humans, and were protective against low-dose aerosol challenge in mice. 14 Importantly, the SAP antigens are highly expressed during hypoxia and starvation, suggesting that they may be induced during the latent phase of the bacilli. 13 , 14 In this report, SAP components were identified as highly expressed during chronic M. tuberculosis in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, Pinto et al . showed that vaccination with ATP sulfurylase conferred significant protection against murine TB and boosted BCG-induced protective immunity in the lung [98] thereby demonstrating that components of sulfate assimilation pathway are promising candidates for inclusion in new vaccines to control TB in humans.…”
Section: Sulfate Import and Activationmentioning
confidence: 99%
“…7 and Supplementary Dataset 3 ). These TRIM27-interacting proteins were mainly involved in the metabolism (such as AtpC, HisG and FabG) 33 34 35 , stress reaction (such as Rv2026c) and intercellular survival (such as LpcC, PtpA, CysK1 and Pks16) 36 37 of Mtb. As expected, Mtb PtpA was among the secreted proteins showing the strongest interaction with TRIM27 ( Fig.…”
Section: Resultsmentioning
confidence: 99%